Bursting into the Image: Towards De-automatization in VR (Cinéma & Cie. Film and Media Studies Journal, 2023)
The art installation Osmose (1995) by Char Davies, one of the most widely discussed media art projects, will be explored in relation to the notion of de-automatization. The de-automatized experience in Osmose will be developed by looking at theories of perception by Arthur Deikman and Maurice Merleau-Ponty, as well as George Stratton’s inverse goggle experiment, Bernard Stiegler’s account of automation, and Gilles Deleuze’s writings on the virtual. The article traces a double act of de-automatization in Davies’ Osmose that occurs due to the indeterminate object relations in the multi-media installation on the one hand, and their intertwinement with the organic sensing body on the other. This leads to an ungearing of one’s habitual perception, that produces a particular relation with the virtual dimension. By outlining the theoretical framework of the intertwining between technical object and bodily experience in Osmose, it becomes possible to speculate on the trajectory of contemporary VR experiences. Whilst the contemporary VR scene still relies heavily on the privileging of the visual dimension, the project We Live in an Ocean of Air by Marshmallow Laser Feast shows how VR environments can ‘leverage on’ emerging technologies to re-produce nuanced deautomatized experiences. De-automatization unravels how the reception of the deautomatized VR image reframes relations between actual and virtual.
Keywords: Char Davies’ Osmose; De-Automatization; Dehabituation; Perception; Lived Body